Preparing for Mars: human sleep and performance during a 13 month stay in Antarctica. Issue 1 (7th November 2018) - Mairesse, Olivier; MacDonald-Nethercott, Eoin; Neu, Daniel; Tellez, Helio Fernandez; Dessy, Emilie; Neyt, Xavier; Meeusen, Romain; Pattyn, Nathalie
Abstract: Study Objectives: Manned spaceflights from Earth to Mars will likely become reality within the next decades. Humans will be exposed to prolonged isolation, confinement, and altered photoperiods under artificial atmospheric conditions, with potential adverse effects on sleep and performance. On Earth, polar environments serve as space analogs to study human adaptation; yet, few studies include polysomnography due to operational constraints. Methods: Polysomnography, self-reported sleepiness and fatigue, and psychomotor performance were measured every 6 weeks in 13 males (" Hivernauts" ) during a 13 month winter-over campaign at Concordia (Antarctica). Stability and robustness of interindividual differences were examined by means of intraclass correlations. Results: Hivernauts present with high-altitude periodic breathing, increased sleep onset latencies, and reduced psychomotor speed. Except for obstructive apneas, all sleep, sleepiness, and psychomotor performance variables remain stable over time. Individual differences in respiratory variables show the highest degree of stability and robustness, followed by fatigue and situational sleepiness, sleep fragmentation, and psychomotor speed, suggesting moderate to substantial trait-like characteristics for these variables. Phase delays are suspected in Hivernauts, both in individuals with imposed and self-selected bedtimes. A significant decline in psychomotor speed over time is observed in the latter group. Conclusions: Space analog conditions such as isolated confinement, extreme photoperiods, and altered atmospheric conditions affect human sleep and performance. However, individual responses to these extreme environmental challenges show large differences and remain relatively stable under prolonged exposure. Ad hoc polysomnographic, including respiratory function monitoring is therefore recommended for selecting eligible candidates for extraterrestrial sojourns.